'How do we not go back to the factory?': Contradictions of urban development for a Latina-led NGO. Issue 6 (2nd November 2017) - Jimenez, Anthony M.; Collins, Timothy W.
Abstract : Urban governance has increasingly been shaped by neoliberalism, leading to the entrenchment of inequality based on intersecting categories of class, race/ethnicity, nation, gender and age. For groups like La Mujer Obrera (LMO), a Latina-led community-based organization that mobilizes against neoliberal development, it stands to reason that eschewing neoliberal practices would be straightforward. Drawing on Bourdieu's concept of symbolic violence and using multiple methods including semi-structured interviews with representatives of LMO and the local state, our case study demonstrates how even those who resist neoliberalism may embrace practices in conformity with it. Our analysis highlights how LMO's entrepreneurial deployment of Latinx culture uneasily situated the organization for some time within the constraints of urban governance arrangements it was established to resist. Findings suggest that community development organizations might benefit by collaborating with others in pressuring state agents to revise criteria guiding development funding decisions, in order to obtain greater material support for pursuing their empowerment goals.